PERTANGGUNGJAWABAN PROFESI PERAWAT TERHADAP KETERLAMBATAN PENANGANAN PASIEN - L Alfies Sihombing; Yeni Nuraeni; Wiwin Triyunarti (Jurnal Hukum Mimbar Justitia, 2022)
Nursing services as a form of professional service and are an integral part of nursing service. Nursing personnel is one of the most important health workers in helping doctors to carry out medical actions. Nurses must carry out nursing care which includes assessment, determination of nursing diagnoses, planning, carrying out nursing actions, and evaluation of care. Nurses in their daily duties deal directly with other medical personnel and the patients they treat. There are demands to serve health responsibly and apply treatment according to the procedures and education they receive. Nursing practice sometimes encounters problems, one of which is delays in handling patients. The nurse's actions are sometimes without the delegation of authority from the doctors and nurses do it based on their experience. Nurses have the authority, namely that a nurse has competence in carrying out professional nursing care to patients, but not taking certain medical actions. Certain medical actions are collaborative activities between doctors and other health workersKeywords: Nursing, Nurse action, Medical action.